Physical facilitating environments – prisons and madrassas as mechanisms and vehicles of violent radicalisation? - Silke, Andrew (I.B. Tauris, 2019)
Prisons and madrassas have both been repeatedly flagged in UK government policy as high risk settings for jihadist radicalisation. Some theoretical models of the radicalisation process have also drawn attention to these spaces. This review found that there have been cases of radicalisation or attempted radicalisation in both prison settings and madrassas in the UK. However, such cases are isolated. While other countries may have different experiences, the research evidence suggests that successful radicalisation is rare in both settings in the UK. The evidence instead stresses the importance of other factors in the radicalisation process, and suggests that physical settings overall appear to be a poor predictor for radicalisation risk. Despite this, it is clear that both types of settings continue to be widely regarded both by the media and within government circles as prominent centres of radicalisation, with the result that policy attention continues to be specifically directed to these settings.
Keywords: terrorism; radicalisation; prison; madrassa